Jeremiah studies: from text and contexts to theology - Fischer, Georg (Forschungen zum Alten Testament, 2020)
Cover -- Titel -- Foreword -- Table of Contents -- Introduction -- Part 1: Foundations: Text and General Issues -- Jeremiah (Book and Person) Hebrew Bible/ Old Testament -- Jeremiah: Septuagint -- A New Understanding of the Book of Jeremiah. A Response to Robert R. Wilson -- Mysteries of the Book of Jeremiah: Its Text and Formulaic Language. A Response to Hermann-Josef Stipp -- Part 2: Intertextuality in Jeremiah -- Section 1: Connections with the Torah -- Fulfilment and Reversal: The Curses of Deuteronomy 28 as a Foil for the Book of Jeremiah -- a ותפשׂי התורה לא ידעוני - The Relationship of the Book of Jeremiah to the Torah -- Foundation and Challenge: Jeremiah's Manifold Use of dtn/r Phraseology and Ideology -- The Book of Jeremiah: Realization of Threats of the Torah - and Also of Promises? -- Section 2: Relationships with the Prophets and Baruch -- Riddles of Reference: "I" and "We" in the Books of Isaiah and Jeremiah: The Relation of the Suffering Characters -- Pro and Contra Zion? A Comparison of the Temple's Role in the Books of Ezekiel and Jeremiah -- Jeremiah's Relations with the "Minor Prophets". A Window into the Formation of the Book of the Twelve -- Baruch, Jeremiah's 'Secretary'? The Relationships between the Book of Jeremiah and the Book of Baruch -- Simulated Similarities: The Intricate Relationship between the Books of Baruch and Jeremiah -- Part 3: Jeremiah's Roles and Message -- Section 1: The Figure of the Prophet -- Jeremiah - "The Prophet Like Moses?" -- Jeremiah, God's Suffering Servant -- The 'Truth' of the Body - Jeremiah's Authentication as a Prophet by his Suffering -- Section 2: Keys to Jeremiah's Proclamation -- Don't Forget Jerusalem's Destruction! The Perspective of the Book of Jeremiah -- From Terror to Embrace - Deliberate Blending of Metaphors in Jeremiah 30-31.